ANALISIS DAMPAK PENGGUNAAN KIT TUTORIAL TERHADAP HASIL BELAJAR MAHASISWA - Aisyah, Siti (LPPM Universitas Terbuka, 2007)
This article discusses whether there are differences in students’ achievement based on materials used in tutorial activities in Penanganan Anak Berkelainan” (Handling Handicap Children) course. The research was conducted in the first semester of 2006 with students of Diploma II PGTK as the samples. Pre- and post-tests were used to assess students’ performance in tutorilas.  In addition, a survey using questionnaire was employed to collect data on students’ perception on the value of the pre- and post-tests in the tutorial activities. A quasi experiment was conducted to figure out the value of pre- and post tests in collecting data on students’ improvement in understanding tutorial activities using tutorial kits. T test shows that there is a statistically significant difference between pre- and post-test scores with score of pre-test is lower than those of post-test. The T test also shows that children’s achievement in experiment group is higher than those in control group